Isotope systematics of Icelandic thermal fluids - Stefansson, Andri; Hilton, David R.; Sveinbjornsdottir, Arny E.; Torssander, Peter; Heinemeier, Jan; Barnes, Jaime D.; Ono, Shuhei; Halldorsson, Saemundur Ari; Fiebig, Jens; Arnorsson, Stefan (Journal of Volcanology and Geothermal Research, 2017)
Thermal fluids in Iceland range in temperature from < 10 °C to > 440 °C and are dominated by water (> 97 mol%) with a chloride concentration from < 10 ppm to > 20,000 ppm. The isotope systematics of the fluids reveal many important features of the source(s) and transport properties of volatiles at this divergent plate boundary. Studies spanning over four decades have revealed a large range of values for δD (− 131 to + 3.3‰), tritium (− 0.4 to + 13.8 TU), δ 18 O (− 20.8 to + 2.3‰), 3 He/ 4 He (3.1 to 30.4 R A ), δ 11 B (− 6.7 to + 25.0‰), δ 13 C ∑ CO 2 (− 27.4 to + 4.6‰), 14 C ∑ CO 2 (+ 0.6 to + 118 pMC), δ 13 C CH 4 (− 52.3 to − 17.8‰), δ 15 N (− 10.5 to + 3.0‰), δ 34 S ∑ S − II (− 10.9 to + 3.4‰), δ 34 S SO 4 (− 2.0 to + 21.2‰) and δ 37 Cl (− 1.0 to + 2.1‰) in both liquid and vapor phases. Based on this isotopic dataset, the thermal waters originate from meteoric inputs and/or seawater. For other volatiles, degassing of mantle-derived melts contributes to He, CO 2 and possibly also to Cl in the fluids. Water-basalt interaction also contributes to CO 2 and is the major source of H 2 S, SO 4 , Cl and B in the fluids. Redox reactions additionally influence the composition of the fluids, for example, oxidation of H 2 S to SO 4 and reduction of CO 2 to CH 4. Air-water interaction mainly controls N 2 , Ar and Ne concentrations. The large range of many non-reactive volatile isotope ratios, such as δ 37 Cl and 3 He/ 4 He, indicate heterogeneity of the mantle and mantle-derived melts beneath Iceland. In contrast, the large range of many reactive isotopes, such as δ 13 C ∑ CO 2 and δ 34 S ∑ S − II , are heavily affected by processes occurring within the geothermal systems, including fluid-rock interaction, depressurization boiling, and isotopic fractionation between secondary minerals and the aqueous and vapor species. Variations due to these geothermal processes may exceed differences observed among various crust and mantle sources, highlighting the importance and effects of chemical reactions on the ...